Efferocytosis and autoimmune disease - Kawano, Mahiru (Int Immunol, 2018)
An enormous number of cells in the body die by apoptosis during development and under homeostasis. Apoptotic cells are swiftly engulfed by macrophages and digested into units. This removal of apoptotic cells is called ‘efferocytosis’. For efferocytosis, macrophages recognize phosphatidylserine (PtdSer) exposed on the cell surface as an ‘eat me’ signal. In healthy cells, PtdSer is exclusively localized to the inner leaflet of the plasma membrane by the action of flippases. When cells undergo apoptosis, caspase cleaves flippases to inactivate them, while it cleaves pro-scramblases to active scramblases, which quickly translocate PtdSer to the cell surface. The PtdSer is then recognized by PtdSer-binding proteins or by PtdSer receptors on macrophages, which subsequently engulf the apoptotic cells. When efferocytosis fails, apoptotic cells can rupture, releasing cellular materials that can evoke an autoimmune response. Thus, a defect in the PtdSer-exposing or PtdSer-recognizing processes triggers autoimmunity, leading to a systemic lupus erythematosus-type autoimmune disease.